Effect of Lactic Fermentation and Cooking on Nutrient and Mineral Digestibility of Peas - Skalickova, Sylvie; Ridoskova, Andrea; Slama, Petr; Skladanka, Jiri; Skarpa, Petr; Smykalova, Iva; Horacek, Jiri; Dostalova, Radmila; Horky, Pavel (Frontiers in Nutrition, 2022)
Peas are prospectively beneficial legumes in the human diet, and especially in a vegan and vegetarian diet, due to their high content of proteins and starch. Unfortunately, their unpopularity in human nutrition is caused by their bloating effects and the content of some antinutritional substances inhibiting the absorption of important nutrients. We bring a comprehensive comparison of the digestibility of pea flour after cooking and the fermentation of pea flour by Lactobacillus plantarum. The digestibility of proteins (total proteins and free amino acids), digestibility of starch (maltose, glucose) and the content of undesirable substances (phytic acid, polyphenols and raffinose) as well as a phytase activity and a mineral content (P, Mg, Mn, Fe, Cu, Zn) were monitored. Our results showed the cooking had negative effects on protein and starch digestibility as well as a release of P, Mg, Mn, Fe, Cu and Zn from the pea flour matrix during digestion. On the contrary, lactic fermentation of pea flour showed beneficial effects on protein bioaccessibility, elimination of raffinose and improvement of P, Mg, Mn, Fe, Cu, and Zn release from the pea flour matrix during digestion. Surprisingly, there was a significant (p < 0.05) increase of Fe concentration in the fermented samples. In terms of phytic acid and phytase, there was not observed any effect after treatments. The concentration of polyphenols was significantly (p < 0.05) reduced after cooking but significantly (p < 0.05) increased in the fermented samples probably due to production of secondary metabolites of L. plantarum. These findings suggest that lactic fermentation of pea flour is a promising culinary pre-treatment which improves pea digestibility.